COMPUTER-AIDED SYSTEM OF THE TECHNOLOGICAL PROCESS CONTROL OF ARC STEEL-MAKING FURNACE ORAKUL - A. Ju. Gapaniuk (Литьë и металлургия)
The main functions of the abovementioned system at planning of melting and the process control are shown